Effects of Cross-Sex Hormone Treatment on Cortical Thickness in Transsexual Individuals. (1st May 2014) - Zubiaurre-Elorza, Leire; Junque, Carme; Gómez-Gil, Esther; Guillamon, Antonio
Abstract: Introduction: Untreated transsexuals have a brain cortical phenotype. Cross-sex hormone treatments are used to masculinize or feminize the bodies of female-to-male (FtMs) or male-to-female (MtFs) transsexuals, respectively. Aim: A longitudinal design was conducted to investigate the effects of treatments on brain cortical thickness (CTh) of FtMs and MtFs. Methods: This study investigated 15 female-to-male (FtMs) and 14 male-to-female (MtFs) transsexuals prior and during at least six months of cross-sex hormone therapy treatment. Brain MRI imaging was performed in a 3-Tesla TIM-TRIO Siemens scanner. T1-weighted images were analyzed with FreeSurfer software to obtain CTh as well as subcortical volumetric values. Main Outcome Measures: Changes in brain CTh thickness and volumetry associated to changes in hormonal levels due to cross-sex hormone therapy. Results: After testosterone treatment, FtMs showed increases of CTh bilaterally in the postcentral gyrus and unilaterally in the inferior parietal, lingual, pericalcarine, and supramarginal areas of the left hemisphere and the rostral middle frontal and the cuneus region of the right hemisphere. There was a significant positive correlation between the serum testosterone and free testosterone index changes and CTh changes in parieto-temporo-occipital regions. In contrast, MtFs, after estrogens and antiandrogens treatment, showed a general decrease in CTh and subcortical volumetric measures and an increase in the volume of the ventricles. Conclusions: Testosterone therapy increases CTh in FtMs. Thickening in cortical regions is associated to changes in testosterone levels. Estrogens and antiandrogens therapy in MtFs is associated to a decrease in the CTh that consequently induces an enlargement of the ventricular system.